IMPLEMENTION OF SHARIA GOVERNANCE IN ISLAMIC BANKING WINDOWS OF REGIONAL BANK IN INDONESIA - Fajar Amtsal; Hartomi Maulana (Islamic Business and Management Journal, 2019)
Abstract: This study aims to analyze how the implementation of good corporate governance in regional bank of islamic banking windows in Indonesia based on Financial Service Authority, and the implementation of sharia governance in regional bank of islamic banking windows in Indonesia in according to the standard of sharia governance issued by IFSB. This study uses secondary data obtained from the annual report of good corporate governance of regional bank of islamic banking windows which has published in 2017. The method used in this study is qualitative with the type research using content analysis from the annual good corporate governance report of regional bank of islamic banking windows in Indonesia. The result of this study indicates that the implementation of good corporate governance at regional bank of islamic banking windows in general have done good corporate governance which is marked with the result of self-assessment of every regional bank of islamic banking windows which on average gets a good predicate. The result of research on the implementation of IFSB standard of sharia governance in general have applied some of the IFSB standards, but there is 1 (one) standard are not implemented by several banks and several standards are not applied to all banks. For futher research it is expected to re-analyze the implementation of sharia governane based on IFSB standardby using other analysis data teqnique to be able to examine the other result of analysis of sharia governance with the new prespectiveKeywords: Islamic Banking; Regional Bank; Sharia Governance; IFSB.